Founding German vocational education: Kerschensteiner, Spranger and Fischer as key figures in the classical German VET theory - Kuhlee, Dina [Verfasser]; Steib, Christian [Verfasser]; Winch, Christopher [Verfasser] (My University, 2022)
„This introduction familiarises the readers of this Special Issue with some important information and arguments that set the life and work of Georg Kerschensteiner, Eduard Spranger and Aloys Fischer in context. In addition, it shows their relevance to current debates and policies in vocational education and training (VET) in both Germany and the Anglophone countries. As a first step, some important concepts in German VET that may cause difficulty in the interpretation for English-speaking readers are introduced and explained. Following from that, an outline of the historical context in which modern German VET was developed is set out and then the place of Kerschensteiner, Spranger and Fischer within that context is described with particular reference to the continuation school, the focus of Kerschensteiner's contribution. Spranger's main contribution was to integrate concern for VET within broader academic issues about education, while Fischer was concerned with young people's transition into the labour force at a time of considerable social and economic change. The introduction concludes with a discussion of the relevance of these thinkers and German VET more generally to the current situation of VET in England, with reference to such topics as ‘academic drift’ and liberal and civic education.“ (authors‘ abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; T 1.2 Historische Berufsbildungsforschung; 370; 300; Berufsbildung; Berufsbildungssystem; Historische Entwicklung; Kerschensteiner, Georg; Spranger, Eduard; Fischer, Aloys; Deutschland; Bundesrepublik Deutschland; England